Development of de novo diabetes in long-term follow-up after bariatric surgery - Nor Hanipah, Zubaidah; Punchai, Suriya; Brethauer, Stacy A.; Schauer, Philip R.; Aminian, Ali (Springer Verlag, 2018)
Introduction: While bariatric surgery leads to significant prevention and improvement of type 2 diabetes, patients may rarely develop diabetes after bariatric surgery. The aim of this study was to determine the incidence and the characteristic of new-onset diabetes after bariatric surgery over a 17-year period at our institution. Methods: Non-diabetic patients who underwent bariatric surgery at a single academic center (1997–2013) and had a postoperative glycated hemoglobin (HbA1c) ≥ 6.5%, fasting blood glucose (FBG) ≥ 126 mg/dl, or positive glucose tolerance test were identified and studied. Results: Out of 2263 non-diabetic patients at the time of bariatric surgery, 11 patients had new-onset diabetes in the median follow-up time of 9 years (interquartile range [IQR], 4–12). Bariatric procedures performed were Roux-en-Y gastric bypass (n = 7), adjustable gastric banding (n = 3), and sleeve gastrectomy (n = 1). The median interval between surgery and diagnosis of diabetes was 6 years (IQR, 2–9). At the last follow-up, the median HbA1c and FBG values were 6.3% (IQR, 6.1–6.5) and 95 mg/dl (IQR, 85–122), respectively. Possible etiologic factors leading to diabetes were weight regain to baseline (n = 6, 55%), steroid-induced after renal transplantation (n = 1), pancreatic insufficiency after pancreatitis (n = 1), and unknown (n = 3). Conclusion: De novo diabetes after bariatric surgery is rare with an incidence of 0.4% based on our cohort. Weight regain was common (> 50%) in patients who developed new-onset diabetes suggesting recurrent severe obesity as a potential etiologic factor. All patients had good glycemic control (HbA1c ≤ 7%) in the long-term postoperative follow-up.